An analysis of the nutritional effects of Schisandra chinensis components based on mass spectrometry technology - Jia, Mengzhen; Zhou, Li; Lou, Yuanyuan; Yang, Xiaoqing; Zhao, Hangyu; Ouyang, Xinshou; Huang, Yanjie (Frontiers in Nutrition, 2023)
Objective: Schisandra chinensis（Turcz.）Baill. (S. chinensis) is a Traditional Chinese medicinal herb that can be used both for medicinal purposes and as a food ingredient due to its beneficial properties, and it is enriched with a wide of natural plant nutrients, including flavonoids, phenolic acids, anthocyanins, lignans, triterpenes, organic acids, and sugars. At present, there is lack of comprehensive study or systemic characterization of nutritional and active ingredients of S. chinensis using innovative mass spectrometry techniques. Methods: The comprehensive review was conducted by searching the PubMed databases for relevant literature of various mass spectrometry techniques employed in the analysis of nutritional components in S. chinensis, as well as their main nutritional effects. The literature search covered the past five years until March 15, 2023. Results: The potential nutritional effects of S. chinensis are discussed, including its ability to enhance immunity, function as an antioxidant, anti-allergen, antidepressant, and anti-anxiety agent, as well as its ability to act as a sedative-hypnotic and improve memory, cognitive function, and metabolic imbalances. Meanwhile, the use of advanced mass spectrometry detection technologies have the potential to enable the discovery of new nutritional components of S. chinensis, and to verify the effects of different extraction methods on these components. The contents of anthocyanins, lignans, organic acids, and polysaccharides, the main nutritional components in S. chinensis, are also closely associated to its quality. Conclusion: This review will provide guidelines for an in-depth study on the nutritional value of S. chinensis and for the development of healthy food products with effective components.